Simulation of pollutants spreading from a sewage outfall in the Rijeka Bay - MRŠA HABER, IVA; LEGOVIĆ, TARZAN; KRANJČEVIĆ, LADO; CUKROV, MARIJAN (Mediterranean Marine Science, 2020)
Results from a 3D numerical simulation of wind-induced currents and pollution spreading from a sewage outfall are described. The goal was to predict seawater sanitary quality in the Rijeka Bay, Adriatic Sea. A sea motion model was coupled with a model of transport and chemical reactions of fecal coliforms (FC), fecal streptococci (FS) and dissolved oxygen. The selected simulation period of 36 hours following wastewater discharge was found to be sufficient for a significant extinction of bacteria. The simulation was carried out for eight wind directions and two intensities (moderate and high). Mesh convergence was obtained. Two mesh sizes were coupled: coarse, for the whole Bay, and fine, for the northern part of the Bay, close to the sewage discharge of the Rijeka city. For all considered wind directions, the pollution plume with a concentration higher than 100 FC and 100 FS per 100 ml of seawater is conveyed mostly parallel to the coast in either north-west or south-east directions. The plume does not rise to the surface but stays at the depth of 10 to 20 meters. This is a consequence of the hydrodynamics of the Rijeka Bay: the bora wind carries the surface water layer out of the Bay through the Middle and Great Gates, while cold water enters the Bay from the layer below the thermocline. During the southern wind (jugo), the situation is reversed: warmer surface water enters the Bay through either the Middle Gate or the Great Gate, while cold seawater exits through the bottom layer, accumulating warmer seawater in the Bay. The conclusion is that the Rijeka city sewage discharge Delta is well-designed, and the microorganism concentration is well within the suggested regulatory range. The discharge site is far enough from the coast, where local streamlines are mostly parallel to the coast, hence the elevated pollution concentration does not come close to swimming and recreational areas. Even if the discharge increases by 50%, which is unlikely in the near future, the pollution at beaches will stay within regulatory boundaries.